Identifikasi Pembelajaran Berbasis Kearifan Lokal Suku Samawa di TK PGRI Kalimango - Sephia Awinda; Muhammad Tahir; Muslihatun Maulidian; Syaiful Musaddat (Mataram University, 2026)
Research interest in local wisdom-based learning among the Samawa people at TK PGRI Kalimango stems from initial observations indicating that elements of local culture have begun to be introduced through simple activities, such as rabana rhythm practice.This study aims to describe the forms, implementation, and recommendations regarding instruction based on the local wisdom of the Samawa people at TK PGRI Kalimango. It employs a qualitative approach within the framework of educational ethnography. The research subjects included the school principal, five teachers, and students' parents. Data collection involved observation, interviews, and documentation. Data analysis was conducted qualitatively, utilizing NVivo software to facilitate the automated processes of data grouping, coding, and organization. The findings indicate that the forms of Samawa local wisdom integrated into the curriculum at TK PGRI Kalimango include the use of the Samawa regional language, traditional attire, oral traditions, traditional arts, traditional games, local cuisine, and traditional Samawa dances. The implementation of this local wisdom-based instruction is systematically planned through programs such as Sabarya and Basebo, as well as through art performances and cultural festivals. Furthermore, the researcher recommends utilizing traditional visual arts specifically the Lonto Engal and Kemang Satange motifs as alternatives for developing local wisdom based instruction in early childhood education.